A Rare Chest Wall Deformity after Usage of a Tissue Expander for Breast Reconstruction. Issue 11 (November 2018) - Kuramoto, Yukiko; Yano, Tomoyuki; Sawaizumi, Masayuki; Tanakura, Kenta; Miyashita, Hiroki
Abstract : Summary: A 2-stage breast reconstruction using a breast tissue expander and prosthesis is a simple method of breast reconstruction with little donor-site morbidity and short surgery time. In this report, we present a rare case of chest wall deformity, which appeared during breast skin expansion with tissue expander. We present a case of a 31-year-old woman who underwent a 2-stage breast reconstruction with a tissue expander and breast prosthesis. She had a former history of autologous microtia reconstruction using costal cartilages to create a framework of the ear at the age of 10. During expansion, the woman developed an abnormal hollowing of the chest wall. Even though it was difficult to select an ideal size for the breast prosthesis, an excellent breast shape was obtained by measuring the actual breast projection that we needed, using ultrasound sonography. The patient was satisfied with the final result. In this case, the patient suffered from a postoperative chest wall deformity due to cartilage harvesting. This unfavorable result highlights the need for careful preoperative evaluation of risk factors that may lead to chest wall deformity when patients will have tissue expansion as a part of breast reconstruction. When thoracic deformity occurs, surgeons should realize that choosing an adequate implant becomes rather difficult. Ultrasound sonography helps surgeons in measuring the actual breast projection preoperatively.